2014
DOI: 10.1161/hypertensionaha.114.03563
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Silent Brain Infarcts in a Mediterranean Cohort of Hypertensives

Abstract: Abstract-Silent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
3
24
1
4
Order By: Relevance
“…From all participants with valid data on serum N‐glycome, 98 subjects presented 1 or more SBIs on MRI (10.1%). Among all factors associated with SBIs in the univariate analysis (Table ) and as reported before, age, male sex, and the presence of microalbuminuria were independent predictors of SBIs in our sample.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…From all participants with valid data on serum N‐glycome, 98 subjects presented 1 or more SBIs on MRI (10.1%). Among all factors associated with SBIs in the univariate analysis (Table ) and as reported before, age, male sex, and the presence of microalbuminuria were independent predictors of SBIs in our sample.…”
Section: Resultssupporting
confidence: 81%
“…A stratified randomization method was used to control for age, sex, and the center from which the subjects were recruited. Additional details on subject selection and baseline procedures have been published elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These risk factors include: age, systolic blood pressure, the use of antihypertensive therapy, diabetes mellitus, cigarette smoking, prior cardiovascular disease (coronary heart disease, cardiac failure, or intermittent claudication), atrial fibrillation, and left ventricular hypertrophy by electrocardiogram. Studies have also shown that FSRP associated with the extent of WML, with silent cerebral infarcts or microbleeds' performance in several cognitive domains and global cognitive decline . This is not surprising when taking into account the above‐mentioned association between subcortical lesions and dysfunctional cognitive domains.…”
mentioning
confidence: 86%